2006
DOI: 10.1074/jbc.m600498200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Substrates of Human Protein-tyrosine Phosphatase PTPN22

Abstract: Stimulation of mature T cells activates a downstream signaling cascade involving temporally and spatially regulated phosphorylation and dephosphorylation events mediated by protein-tyrosine kinases and phosphatases, respectively. PTPN22 (Lyp), a non-receptor protein-tyrosine phosphatase, is expressed exclusively in cells of hematopoietic origin, notably in T cells where it represses signaling through the T cell receptor. We used substrate trapping coupled with mass spectrometry-based peptide identification in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(215 citation statements)
references
References 47 publications
6
196
1
4
Order By: Relevance
“…1). Previous studies showed that Lyp preferentially dephosphorylates Lck at Tyr(P) 397 in the activation loop over the autoinhibitory Tyr(P) 505 at its C terminus (11,22). Consistent with this finding, the k cat /K m value for the Lck Tyr 394 peptide (Ac-ENDEpYTARE-NH 2 ) is 10.3-fold higher than that of the Tyr 505 peptide (Ac-TEPQpYQPGE-NH 2 ) (Table 1).…”
supporting
confidence: 77%
“…1). Previous studies showed that Lyp preferentially dephosphorylates Lck at Tyr(P) 397 in the activation loop over the autoinhibitory Tyr(P) 505 at its C terminus (11,22). Consistent with this finding, the k cat /K m value for the Lck Tyr 394 peptide (Ac-ENDEpYTARE-NH 2 ) is 10.3-fold higher than that of the Tyr 505 peptide (Ac-TEPQpYQPGE-NH 2 ) (Table 1).…”
supporting
confidence: 77%
“…67), and a proteomic approach has been used for the identification of substrates of the PTP, PTPN22, by MS analysis of proteins associated with a substrate-trapping mutant (68). In this study, we demonstrate that a substrate-trapping form of Cdc14 can be used to identify and validate novel substrates, including Bni1, Bnr1, and Kar9.…”
Section: Discussionmentioning
confidence: 93%
“…This mutant was used to exclude interactions caused by the substrate trapping activity of LYP (10). We found that ⌬288LYP is able to form a complex with Csk as well as Lck but not with other PTKs in T cells.…”
Section: Binding Of Csk To Lyp Does Not Directlymentioning
confidence: 99%